Peran Dewan Pengawas Syariah Pada Pembiayaan Murabahah Di BMT Nurul Uswah MWC NU Majenang - Lu’yan, Hanin Nur Farohah (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2022)
BMT Nurul Uswah is one of the Islamic financial institutions that applies sharia principles in its operational activities. Therefore, at BMT Nurul Uswah there is a DPS in charge of overseeing activities to ensure the fulfillment of sharia compliance in BMT operations, one of which is financing products with Murabahah contracts. The problem studied is how the role of the Sharia Supervisory Board in the implementation of sharia compliance in the practice of Murabahah financing is at BMT Nurul Uswah MWCNU Majenang. The method used is field research with a qualitative approach. The results of the first study indicate that the practice of Murabahah financing at BMT Nurul Uswah is not in accordance with sharia compliance because there are characteristics that indicate the existence of gharar and usury. Second, the role of DPS in implementing sharia compliance in the Murabahah contract at BMT Nurul Uswah is good but not optimal, due to the lack of independence and firmness in making decisions because structurally this division is under the control of the founder of BMT NU.